Pro Asp.net MVC 3 framework - Freeman, Adam, 1972- (Expert's voice in .NET., 2011)
Looks at the features of the ASP.NET MVC 3 framework, covering such topics as routing, model binding, views, scripting, security, deployment, and WebForms.